Reimagining Teacher Education in India: Evaluating NEP 2020’s Impact and Implementation Challenges - Manisha Tiwari (International Journal of Education Sciences, 2024)
India's educational system has undergone a substantial change with the implementation of the National Education Policy (NEP) 2020, which places a special focus on enhancing teacher preparation. The policy, which was endorsed by the Union Cabinet on July 29, 2020, was crafted by a commission led by former ISRO Chairman Dr. K. Kasturirangan, who defined the vision for the country’s updated education system. The NEP addresses various challenges within the current education system, including quality, affordability, equity, access, and accountability. This paper examines the significance of teacher education as outlined in NEP 2020 and the challenges encountered during its implementation. By reviewing existing literature and policy documents, this research underscores the essential role of well-trained teachers in realizing educational reforms and identifies possible obstacles to effective teacher education. The paper also includes a number of progressive proposals on different aspects of higher education. These proposals include developing quality universities and colleges, institutional restructuring and consolidation, promoting more holistic and multidisciplinary education, creating optimal learning environments and student support systems, transforming the regulatory framework, increasing the use of advanced technology and its integration, and enhancing online and digital education. The draft of the policy is divided into four parts: Part I: School Education, Part II: Higher Education, Part III: Other Key Areas of Focus and Part IV: Implementation. This paper specifically focuses on teacher education, which is covered in Part II of the Higher Education section.
Keywords: Education policy; Indian higher education system; NEP 2020; opportunities & challenges; research and innovation focus; teacher education